[tex] \begin{cases} x + 3y = 11\\ 2x - 4y = 2\end{cases}[/tex]
[tex]\begin{cases}x = 11 - 3y \\ 2x - 4y = 2 \end{cases}[/tex]
[tex]\begin{cases} x = 11 - 3y \\ 2(11 - 3y) - 4y = 2\end{cases}[/tex]
[tex]\begin{cases}x = 11 - 3y \\ 22 - 6y - 4y = 2 \end{cases}[/tex]
[tex]\begin{cases} x = 11 - 3y \\ - 10y = - 20 | \div ( - 10) \end{cases}[/tex]
[tex]\begin{cases} x = 11 -3y \\ y = 2 \end{cases}[/tex]
[tex]\begin{cases} x = 11 - 3 \times 2 \\ y = 2\end{cases}[/tex]
[tex]\begin{cases}x = 11 - 6 \\ y = 2 \end{cases}[/tex]
[tex]\begin{cases} x = 5 \\ y = 2\end{cases}[/tex]